PENGARUH MUTASI, PROMOSI DAN KOMPENSASI TERHADAP KINERJA PEGAWAI TETAP MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING DI PT. BPR TRIDANA KENCANA SITUBONDO - Malik Fahri Mustofa; Siti Soeliha; Ida Subaida (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
The purpose of this study is to determine the Effect of Mutation, Promotion and Compensation on Permanent Employee Performance Through Job Satisfaction as an Intervening Variable at PT. BPR Tridana Kencana Situbondo. The sampling technique used in this study was a saturated sample of 37 permanent employees. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM) The results of the study showed that Mutation had a significant positive effect on Job Satisfaction, Promotion had a significant positive effect on Job Satisfaction, Compensation had a positive but not significant effect on Job Satisfaction, Mutation had a significant negative effect on Employee Performance, Promotion had a significant negative effect on Employee Performance, Compensation had a positive but not significant effect on Job Satisfaction, Job Satisfaction had a significant positive effect on Employee Performance, Mutation had a significant positive effect on Employee Performance through Job Satisfaction, Promotion had a positive effect significant on employee performance through job satisfaction, compensation has a positive but not significant effect on employee performance through job satisfaction